DIARY OF A COLLECTIVE OF SUOTHERN BODIES IN NORTHERN TERRITORIES - Gildemeister Flores, Marlene; Paredes, Andrea Belén S.; Patiño Martínez, Ana María; Sanchez Mora, Mayra Lucía; Bascones Cornejo, Brenda Lucía (Instituto Regional de Planeamiento y Hábitat (RPHA), Unidad Doble dependencia CONICET y UNSJ, 2023)
This piece has been made in the time stolen from studies and multiple employment in the Kingdom of Spain (the master's house). We manifest that this is also our place, where we feel and create our Pacha-Calendar in communion with our ancestral memory. They will no longer take away our memories, despite racist capitalism that does everything to take them away from us. Our diasporic bodies long for togetherness and that is our rebellion.